Segregation of Spontaneous and Training Induced Recovery from Visual Field Defects in Subacute Stroke Patients - Bergsma, Douwe P.; Elshout, Joris A.; van den Berg, Albert V. (Frontiers in Neurology, 2017)
Whether rehabilitation after stroke profits from an early start is difficult to establish as the contributions of spontaneous recovery and treatment are difficult to tease apart. Here we use a novel training design to dissociate these components for visual rehabilitation of sub-acute stroke patients with visual field defects such as hemianopia. Visual discrimination training was started within 6 weeks after stroke in 17 patients. Spontaneous and training-induced recovery were distinguished by training one half of the defect for 8 weeks, while monitoring spontaneous recovery in the other (control) half of the defect. Next, trained and control regions were swapped and training continued for another 8 weeks. The same paradigm was also applied to 7 chronic patients for whom spontaneous recovery can be excluded and changes in the control half of the defect point to a spill-over effect of training. In both groups field stability was assessed during a no-intervention period. Defect reduction was significantly greater in the trained part of the defect than in the simultaneously untrained part of the defect irrespective of training onset (p = 0.001). In sub-acute patients training contributed about twice as much to their defect reduction as the spontaneous recovery. Goal Attainment Scores were significantly and positively correlated with the total defect reduction (p = 0.01), reading speed was significantly and positively correlated with the defect reduction induced by training (epoch 1: p = 0.0044; epoch 2: p = 0.023). Visual training adds significantly to the spontaneous recovery of visual field defects, both during training in the early and the chronic stroke phase. However, field recovery as a result of training in this sub-acute phase was as large as in the chronic phase. This suggests that patients benefitted primarily of early onset training by gaining access to a larger visual field sooner.